Therapeutic oxygen delivery by perfluorocarbon-based colloids - Krafft, Marie Pierre; Riess, Jean G. (Advances in colloid and interface science, 2021)
After the protocol-related indecisive clinical trial of Oxygent, a perfluorooctylbromide/phospholipid nanoemulsion, in cardiac surgery, that often unduly assigned the observed untoward effects to the product, the development of perfluorocarbon (PFC)-based O2 nanoemulsions (“blood substitutes”) has come to a low. Yet, significant further demonstrations of PFC O2-delivery efficacy have continuously been reported, such as relief of hypoxia after myocardial infarction or stroke; protection of vital organs during surgery; potentiation of O2-dependent cancer therapies, including radio-, photodynamic-, chemo- and immunotherapies; regeneration of damaged nerve, bone or cartilage; preservation of organ grafts destined for transplantation; and control of gas supply in tissue engineering and biotechnological productions. PFC colloids capable of augmenting O2 delivery include primarily injectable PFC nanoemulsions, microbubbles and phase-shift nanoemulsions. Careful selection of PFC and other colloid components is critical. The basics of O2 delivery by PFC nanoemulsions will be briefly reminded. Improved knowledge of O2 delivery mechanisms has been acquired. Advanced, size-adjustable O2-delivering nanoemulsions have been designed that have extended room-temperature shelf-stability. Alternate O2 delivery options are being investigated that rely on injectable PFC-stabilized microbubbles or phase-shift PFC nanoemulsions. The latter combine prolonged circulation in the vasculature, capacity for penetrating tumor tissues, and acute responsiveness to ultrasound and other external stimuli. Progress in microbubble and phase-shift emulsion engineering, control of phase-shift activation (vaporization), understanding and control of bubble/ultrasound/tissue interactions is discussed. Control of the phase-shift event and of microbubble size require utmost attention. Further PFC-based colloidal systems, including polymeric micelles, PFC-loaded organic or inorganic nanoparticles and scaffolds, have been devised that also carry substantial amounts of O2. Local, on-demand O2 delivery can be triggered by external stimuli, including focused ultrasound irradiation or tumor microenvironment. PFC colloid functionalization and targeting can help adjust their properties for specific indications, augment their efficacy, improve safety profiles, and expand the range of their indications. Many new medical and biotechnological applications involving fluorinated colloids are being assessed, including in the clinic. Further uses of PFC-based colloidal nanotherapeutics will be briefly mentioned that concern contrast diagnostic imaging, including molecular imaging and immune cell tracking; controlled delivery of therapeutic energy, as for noninvasive surgical ablation and sonothrombolysis; and delivery of drugs and genes, including across the blood-brain barrier. Even when the fluorinated colloids investigated are designed for other purposes than O2 supply, they will inevitably also carry and deliver a certain amount of O2, and may thus be considered for O2 delivery or co-delivery applications. Conversely, O2-carrying PFC nanoemulsions possess by nature a unique aptitude for 19F MR imaging, and hence, cell tracking, while PFC-stabilized microbubbles are ideal resonators for ultrasound contrast imaging and can undergo precise manipulation and on-demand destruction by ultrasound waves, thereby opening multiple theranostic opportunities. [Display omitted] •Fluorocarbon nanoemulsions effectively deliver oxygen to tissues, relieve hypoxia.•Fluorocarbon-stabilized microbubbles provide an alternate oxygen delivery option.•Phase-shift emulsions combine enhanced circulation half-life and tumor penetration.•Proper choice of fluorocarbon, shell components, dispersion technology is critical.•PFC colloids improve diagnostic imaging, deliver therapeutic energy, drugs, genes.